Mitigation of Social Impacts of Alternative Road Development Plans Based on Local Wisdom in West Sumatra, Indonesia - null Priyambodo; Kristian Buditiawan; Agung Budi Irawan; Dendy Setyawan; Herrukmi Septa Rinawati; null Afriyanni; null Momon; Elsa Yolarita; Vivi Ukhwatul Khasanah Masbiran; Imbang Dananjaya (The Scientific World Journal)
Infrastructure development, especially roads, is hampered by the fact of rejection based on urgency and attachment to the Ulayat land of the local community. Therefore, further models are needed in the form of mitigation based on culture and local wisdom to avoid conflicts and land disputes and changes in their use. This study aims to identify the social impacts of the bypass Amor Road construction and its mitigation strategies based on the perceptions of the community and stakeholders. This research study uses a descriptive qualitative research method. Data collection techniques were carried out through documentation studies, observation, and in-depth interviews. The data analysis technique was carried out using SIA (social impact analysis). SIA helps the community, government, and private sector to better understand and anticipate possible social problems and the changes they bring about as a result of the construction of the bypass Amor road. The results of the study conclude that the success of road construction depends on the government’s mitigation strategy in adopting local values that live in the community which is then followed by the existence of a foundation and expansion of the fulfilment of community interests. This study recommends three things, namely, (1) conduct intensive and responsive socialization and approach; (2) approach community involvement through a community-based approach and traditional leaders; and (3) prepare alternative livelihoods based on community interest, local potential, market opportunities, and financial feasibility as well as providing capital for businesses.